Incidence of Brucella infection in various livestock species raised under the pastoral production system in Isiolo County, Kenya - Njeru, Josiah; Nthiwa, Daniel; Akoko, James M.; Oyas, H.; Bett, Bernard K. (Springer, 2021)
Background: We implemented a longitudinal study to determine the incidence of Brucella infection in cattle, camels, sheep and goats that were being raised in a pastoral area in Isiolo County, Kenya. An initial cross-sectional survey was implemented to identify unexposed animals for follow up; that survey used 141 camels, 216 cattle, 208 sheep and 161 goats. Sera from these animals were screened for Brucella spp. using the Rose Bengal Plate test (RBPT), a modified RBPT, and an indirect multispecies Enzyme Linked Immunosorbent Assay (iELISA). Results of RBPT and iELISA were interpreted in parallel to determine seroprevalence. A total of 30 camels, 31 cattle, 22 sheep and 32 goats that were seronegative by all the above tests were recruited in a subsequent longitudinal study for follow up. These animals were followed for 12 months and tested for anti-Brucella antibodies using iELISA. Seroconversion among these animals was defined by a positive iELISA test following a negative iELISA result in the previous sampling period. All seropositive samples were further tested using real-time PCR-based assays to identify Brucella species. These analyses targeted the alkB and BMEI1162 genes for B. abortus, and B. melitensis, respectively. Data from the longitudinal study were analysed using Cox proportional hazards model that accounted for within-herds clustering of Brucella infections. Results: The overall incidence rate of Brucella infection was 0.024 (95% confidence interval [CI]: 0.014-0.037) cases per animal-months at risk. Brucella infection incidence in camels, cattle, goats and sheep were 0.053 (0.022-0.104), 0.028 (0.010-0.061), 0.013 (0.003-0.036) and 0.006 (0.0002-0.034) cases per animal-month at risk, respectively. The incidence rate of Brucella infection among females and males were 0.020 (0.009-0.036) and 0.016 (0.004-0.091), respectively. Real-time PCR analyses showed that B. abortus was more prevalent than B. melitensis in the area. Results of multivariable Cox regression analysis identified species (camels and cattle) as an important predictor of Brucella spp. exposure in animals. Conclusions: This study estimated an overall brucellosis incidence of 0.024 cases per animal-months at risk with camels and cattle having higher incidence than sheep and goats. These results will inform surveillance studies in the area.